A case study of repetitive transcranial magnetic stimulation for cryptococcal meningitis combined with cognitive impairment - Liu, Yuanbiao; Fan, Lei; Jiang, Xinlin; Lu, Yi; Li, Yige (Frontiers in Human Neuroscience, 2022)
Cryptococcal meningitis (CM) is a central nervous system disease caused by a novel Cryptococcus that leads to subacute or chronic inflammatory changes in the nervous system. In this paper, we present a 72-year-old woman with cryptococcal meningitis and severe cognitive impairment and disabilities. Cognitive assessment indicated that although her cognitive function was found impaired, especially executive function, it largely improved after receiving anti-infectious and repetitive transcranial magnetic stimulation (rTMS) therapy, which can reduce the levels of inflammatory cytokines such as IL-8, IL-10, and TNF-α. We argue that this case provided a novel method of treatment for patients with CM in conjunction with cognitive impairments.